Intelligent Traffic Management Systems Using Image Processing Techniques - Shaimaa Abbas Fahdel Al-Abaidy, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The world's population and the multitude of cars on the road today are both gaining popularity. Most countries in the world are currently experiencing traffic congestion. Ineffective traffic management, which results in regular traffic congestion at major intersections, is one of the major causes of such issues, which includes environmental pollution, traffic injuries, health losses, and time wasted. As a result, to efficiently control traffic congestion on streets, highways, and roads, a successful management system is required. The aim of this study was to compare and contrast various traffic electronic systems and their feature extraction techniques in order to effectively manage pollution level. Based on data from video camera images of roads and image processing techniques used to monitor traffic road traffic congestion, we constructed a framework for a traffic management system.